The role of titles in strengthening the legitimacy of the Mamluk authority (Al-Zahir Baybars inscriptions in the buildings of the Levant as a model) - حسن, غادة (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Archaeological inscriptions on religious and civil buildings are an important source of Islamic history. They are authentic documents whose value is not easy to challenge. They played a key role in the policy of the Mamluk Sultan Al-Zahir Baybars and the Mamluk sultans who came after him in establishing the legitimacy of their rule in Egypt and the Levant, and confirming their leadership over other regions in the Islamic Arab Mashreq. This study aims to shed light on the titles engraved on Baibars in some religious and civil buildings in the Levant, and its role in presenting the Sultan as the ideal Muslim ruler and fighter for Islam. The research also shows the role of nicknames in evoking the foundations on which Baibars built his image and legitimacy in exercising power.